Smaller than small comparatives: the case of Basque - Vela-Plo, Laura (Borealis – An International Journal of Hispanic Linguistics, 2018)
Adjectival comparatives like txiki baino txikiago ‘smaller than small’ in Basque exhibit some striking properties that present a challenge for previous analyses of inequality comparatives. The research on this unstudied type of adjectival comparatives in Basque – henceforth small comparatives – is especially interesting due to the rich morphology and freedom of word order that Basque displays. These two properties are vital for the testing of the hypotheses on the structure of these comparatives. First, the examination of the underlying structure of the standard of comparison reveals that these adjectival modifiers are inequality comparatives with a phrasal standard. Second, the study of the extraction constraints of the standard and the particular distribution of small comparatives evidence the fact that the standard marker in these comparatives behaves as a coordinating conjunction, and that these modifiers can appear inside a Determiner Phrase, in contrast with previously analysed adjectival comparatives. These properties are explained by assuming the functional analysis of adjectives and comparative markers (-ago ‘-er, more’), and proposing a coordination analysis of these phrasal comparatives. The study of small comparatives hence shows that the coordination analysis of comparative structures is necessary not only for clausal comparatives (Napoli & Nespor 1983 for Italian; Sáez 1992 for Spanish; and Lechner 2004 for English and German) but also for phrasal comparatives such as small comparatives.